Integrating Bumi Raflesia Culinary Context Assisted by Scratch to Support Mathematical Values in Ratio Concepts - Lucy Asri Purwasi; Nyimas Aisyah; Yusuf Hartono; Budi Mulyono (Mathematics Education Journal, 2026)
Understanding the basic concepts of ratio topics and internalizing mathematical values play a crucial role in improving the quality of learning. Mathematical values are closely related to mathematical materials, problems, and solutions relevant to everyday life. Similarly, ratio topics are often found in advanced mathematics and everyday life. However, although ratio teaching has been widely practiced, there is still a research gap in connecting local cultural contexts with mathematics teaching, while also implementing digital technology to support student understanding. The purpose of this study was to design a learning trajectory for the topic of ratio concepts using the principles and characteristics of PMRI with the culinary context of Bumi Raflesia, assisted by the Scratch. The study employed design research of the validation studies type, consisting of three phases: preliminary design, design experiment, and retrospective analysis. Data were collected using tests, interviews, and observation. This activity involved seventh-grade junior high school students in Bengkulu City. The resulting learning trajectory consisted of four activities: observing ingredient measurements using the Scratch application, identifying quantitative relationships between ingredients, determining ingredient quantities based on ratios, and completing ingredient comparison tables. The research findings indicate that the learning trajectory internalized students' mathematical values. These findings provide theoretical contributions to the design of learning trajectories by integrating local cultural contexts and digital technologies to enhance realistic and meaningful learning experiences.